Coronary arterial disease after electroconvulsive therapy: a case report - Rodrigues,Nataly Pimentel (2015)
Objectives Unipolar depression (UPD) is a leading cause of global burden of diseases, particularly among the elderly, whose treatment may be challenging. In such cases, ECT is often recommended due to its safety and efficacy. This report presents a case of a 67-year-old male inpatient that developed a rare cardiac complication during ECT. Methods Clinical case report with patient’s consent and bibliographic review. Results A 67-year-old male inpatient with recurrent severe psychotic depression was hospitalized and ECT was indicated after failure of the pharmacological treatment. A comprehensive clinical pre-evaluation revealed only nonspecific ST-segment changes in electrocardiogram. During the 7th ECT session, it was observed transitory ST-segment depression followed by a discrete increase of plasma troponin I. Severe tri-vessel coronary artery stenosis was found and a percutaneous coronary angioplasty was performed, with satisfactory psychiatric and cardiac outcomes. Conclusions Unipolar depression (UPD) and cardiovascular disease are often coexistent conditions, especially among the elderly. In the current case, myocardial ischemia was detected lately during ECT therapy and its treatment allowed the UPD treatment to be completed adequately.